2020
DOI: 10.1525/elementa.409
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of regional ozone in China: implications for human health and ecosystem impacts

Abstract: detrimental to human health and vegetation (REVIHAAP, 2013; CLRTAP, 2016). Atmospheric ozone can only be formed in photochemical reactions. In the stratosphere, ozone is produced and sustained by the Chapman mechanism and catalytically destroyed by active species, such as OH, NO, and halogenated species (Solomon, 1999). A simulation study by Lelieveld and Dentener (2000) suggests that more than 85% of tropospheric ozone originates from photochemical oxidation of volatile organic compounds (VOCs), CO, and CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 65 publications
2
53
0
Order By: Relevance
“…It is inconsistent with satellite NO2 data shown in Fig 5 (and NOx emission inventory) which indicate gradual decrease in NOx emission after 2011. Recently reported surface measurements at two rural sites near Beijing (Shangdianzi and Gucheng) also did not observe sudden ozone drop around 2011/12 (Xu et al, 2020). I suggest comparing satellite observed tropospheric ozone to verify the sudden change observed in the present study.…”
Section: Major Commentssupporting
confidence: 81%
See 1 more Smart Citation
“…It is inconsistent with satellite NO2 data shown in Fig 5 (and NOx emission inventory) which indicate gradual decrease in NOx emission after 2011. Recently reported surface measurements at two rural sites near Beijing (Shangdianzi and Gucheng) also did not observe sudden ozone drop around 2011/12 (Xu et al, 2020). I suggest comparing satellite observed tropospheric ozone to verify the sudden change observed in the present study.…”
Section: Major Commentssupporting
confidence: 81%
“…. Please note that recent studies have shown levelling off/decrease in surface ozone levels in rural areas of eastern China and in outflow of eastern China air masses (Xu et al, 2020;Wang et al, 2019).…”
Section: Minor Commentsmentioning
confidence: 99%
“…Table S1 also presents the observed HONO mixing ratios at two coastal sites in Hong Kong (Z. Y. Xu et al, 2015), but their levels were substantially underpredicted because capturing such coastal characteristics is challenging for the model, due to its low horizontal resolution (36 km).…”
Section: Comparison Of the Simulated And Observed Reactive Gasesmentioning
confidence: 99%
“…Ozone concentrations from the Earth's surface up to ∼ 30 km were measured over Beijing using an ozonesonde developed by the Key Laboratory of Middle Atmosphere and Global Environment Observation of the Institute of Atmospheric Physics (IAP) (Zhang et al, 2014). The IAP ozonesonde is based on an electrochemical method which is well documented in previous studies (Wang et al, 2003;Xuan et al, 2004;Zheng and Li, 2005). The ozonesonde has previously been compared with the widely used electrochemical concentration cell (ECC) developed by Komhyr (1969) and the Brewer spectrophotometer (Zhang et al, 2014) and was able to capture the ozone profile.…”
Section: Ozonesondementioning
confidence: 99%
“…Air quality controls have been implemented in China as a result of the recent increases in atmospheric pollutants, especially in the North China Plain, and the emissions of SO 2 and NO x have been successfully reduced in recent years (Ma et al, 2016;van der A et al, 2017;Li et al, 2017). Recent studies have shown a levelling off/decrease in surface ozone levels in rural areas of eastern China and in the outflow of eastern China air masses (Xu et al, 2020;. Using the Infrared Atmospheric Sounding Interferometer (IASI) on board the European Space Agency's (ESA) MetOp series of polar orbiting satellites, together with surface and ozonesonde measurements, Dufour et al (2018) reported the trend in tropospheric ozone concentrations over the North China Plain for the time period 2008-2016.…”
Section: Introductionmentioning
confidence: 99%